INITIATING SMART PUBLIC TRANSPORTATION IN LAGOS: SETTING THE TONE FOR AFRICAN CITIES - Desmond AMIEGBEBHOR; Boluwatife POPOOLA (Journal of Construction Project Management and Innovation)
After several initiatives in public transportation primarily anchored by both the private and public sector which were short-lived, the informal sector comprising two-wheeler motor cycles, the “danfoes” and “molues” being operated by the (National Union of Road Transport Workers and the Road Transport Employers’ Association of Nigeria) became the dominate operator of urban bus operations in Nigerian urban cities including Lagos. With the growth in population and economic activities making Lagos a mega city, the breach in urban transport operations became ostensible. It therefore became imperative to introduce initiative particularly quick win interventions that would deliver smart mobility innovations for efficient movement of the commuting public. Smart public transportation is essential to meet the challenges of urbanization in Lagos and other African cities. A detailed analysis as encapsulated in the Bus Route Network study is required to determine travel pattern, route alignments, infrastructure gap, transit service type (Bus Rapid Transit, Rail or regulated bus system) and technology type that would be required to guide decision makers and politicians. For African cities, however, there is need to domesticate our public transportation requirements for implementation and gradually ramp up with the deployment of mobility application technology like Intelligent Transport Systems comprising mobile apps, electronic ticketing amongst others.